Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae) - Sanabria-Urbán, Salomón; Song, Hojun; Oyama, Ken; González-Rodríguez, Antonio; Castillo, Raúl Cueva Del (Zootaxa, 2017)
The genus Sphenarium Charpentier, 1842 comprises the most diverse group of the New World Pyrgomorphidae. These grasshoppers show an extensive variation in external morphology, and are culturally and economically important for Mexican people since pre-Hispanic times. Nevertheless, the taxonomy of Sphenarium has been chaotic and remained incompletely resolved until now. Following an integrative taxonomic framework, we infer the number of species in this genus by species delimitation based on morphological, phylogenetic, and geographic information. Based on our results, we revise the genus and redefine 9 species and describe 8 new species (S. adelinae sp.n., S. crypticum sp.n., S. infernalis sp.n., S. miztecum sp.n., S. occidentalis sp.n., S. tarascum sp.n., S. totonacum sp.n. and S. zapotecum sp.n.). Moreover, we update the knowledge of the evolutionary relationships and biogeographic patterns of Sphenarium species. Our results also demonstrate the importance of historic geological and climatic events on the lineage diversification of this genus. Different levels of morphological and genetic differentiation among species suggest a complex interplay between evolutionary forces during the evolution of these neotropical grasshoppers.